1985
DOI: 10.3109/00207458509149134
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Effects in Neuropsychological Assessment

Abstract: The group selected for this evaluation consisted of 109 normal people with an average age of 25, coming from two different sociocultural levels (high and low) of Mexico City. All were completely evaluated by Luria's battery for neuropsychological assessment, adapted by Ardila, Ostrosky, and Canseco, 1981. This group of tests measures nine different areas: Motor Functions, Somatosensory Knowledge, Auditory Knowledge, Visuospatial Knowledge, Cognitive Processes, Language, Reading, Writing and Basic Calculations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
7

Year Published

1989
1989
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 11 publications
1
20
0
7
Order By: Relevance
“…No nomear artigo de supermercado, os resultados corroboram estudos que encontraram diferenças significativas entre diferentes grupos educacionais, em testes de fluência verbal 1 4 , 2 2 -2 5 que, geralmente, fazem parte da avaliação da linguagem. As habilidades verbais, por sua vez, são mais dependentes da educação do que as não-verbais, até porque, na escola, é através da linguagem que aprendemos noções e conceitos; logo, encontraríamos diferenças para os analfabetos, na maioria das áreas de linguagem 22 . O item seqüência alternada de Δ e  pode estimar a flexibilidade mental (Tabela 3), que parece mais desenvolvida e necessária nos indivíduos provenientes de centros urbanos, geralmente, mais escolarizados e que convivem com uma quantidade maior e mais rápida de mudanças, do que em pessoas que passam a maior parte de suas vidas em comunidades pequenas e pacatas 14 .…”
Section: Discussionunclassified
“…No nomear artigo de supermercado, os resultados corroboram estudos que encontraram diferenças significativas entre diferentes grupos educacionais, em testes de fluência verbal 1 4 , 2 2 -2 5 que, geralmente, fazem parte da avaliação da linguagem. As habilidades verbais, por sua vez, são mais dependentes da educação do que as não-verbais, até porque, na escola, é através da linguagem que aprendemos noções e conceitos; logo, encontraríamos diferenças para os analfabetos, na maioria das áreas de linguagem 22 . O item seqüência alternada de Δ e  pode estimar a flexibilidade mental (Tabela 3), que parece mais desenvolvida e necessária nos indivíduos provenientes de centros urbanos, geralmente, mais escolarizados e que convivem com uma quantidade maior e mais rápida de mudanças, do que em pessoas que passam a maior parte de suas vidas em comunidades pequenas e pacatas 14 .…”
Section: Discussionunclassified
“…We cannot presuppose a priori that foreign populations scores are necessarily valid due to the previously discussed variables involved. Individuals with low instruction, totally functional in their routines, can and frequently do present performances which overlap those of patients with cerebral lesion when submitted to neuropsychological evaluation, increasing the probability of a mistaken diagnosis if the appropriate corrections are not made (15)(16)(17)(18). Furthermore, the intuitive assumption that lower efficiency is expected from the population of lower educational level conversely leads to underestimation of real pathological data.…”
Section: Overall Analysismentioning
confidence: 99%
“…Garcia and Guerreiro (1983) showed that illiterate subjects without brain disease scored below their literate controls in subtests of the Wechsler Memory Scale, in a questionnaire for daily life events, in Raven's Coloured Matrices and in block design (WAIS). Ostrosky-Solis et al (1985, 1986) presented a neuropsychological diagnostic battery to 109 normal subjects from two sociocultural levels and found that the most sensitive items were those that involved the use of complex conceptual aspects of language and the organisation of motor sequences and motor programmes in general. Ardila et al (1989) and Rosselli et al (1990) reported the results of a large test battery administered to extreme educational groups (non brain-lesioned illiterates and professionals).…”
Section: Illiteracy and Other Aspects Of Neuropsychologymentioning
confidence: 99%